Silencing of the CrkL gene reverses the doxorubicin resistance of K562/ADR cells through regulating PI3K/Akt/MRP1 signaling. Issue 8 (11th June 2021) - Yu, Jiang; Chen, Wen‐XU; Xie, Wen‐Jing; Chen, Rong‐Wei; Lin, Dan‐Qi; You, Wei‐Wei; Ye, Wei‐Lin; Zhang, Hong‐Qin; Lin, Dong‐Hong; Xu, Jian‐Ping
Abstract: Background: Doxorubicin is a first‐line chemotherapy agent on human myelogenous leukemia clinical treatment, but the development of chemoresistance has largely limited curative effect. In this study, we aimed to evaluate the biological function and molecular mechanisms of CrkL to Doxorubicin resistance. Methods: Quantitative reverse transcription‐PCR (qRT‐PCR) assay was performed to examine the expression of CrkL in K562 and K562/ADR cells. The expression of CrkL was silenced through RNA interference technology. MTT assay and flow cytometry were performed to detect the proliferation inhibition and apoptosis rate after CrkL siRNA transfection. The protein expression changes of PI3K/AKT/MRP1 pathway induced by CrkL siRNA were observed by Western Blot assay. Xenograft tumor model was carried out to observe tumor growth in vivo. Results: We observed that silencing of CrkL could effectively increase apoptosis rate induced by doxorubicin and dramatically reversed doxorubicin resistance in K562/ADR cells. Further studies revealed knockdown CrkL expression suppressed PI3K/Akt/MRP1 signaling, which indicated CrkL siRNA reversed doxorubicin effect through regulating PI3K/Akt/MRP1 pathway. In addition, overexpression of MRP1 could evidently reduce apoptosis rate and reversed the inhibitory effects of doxorubicin resistance caused by CrkL siRNA on K562/ADR cells. Finally, in vivo experiments revealed that CrkL silencing acted a tumor‐suppressing role in myelogenous leukemia via regulating PI3K/Akt/MRP1 signaling. Conclusion: Together, we indicated that CrkL is up‐regulated in myelogenous leukemia cells and silencing of CrkL could reverse Doxorubicin resistance effectively. These results show a potential novel strategy for intervention chemoresistance in myelogenous leukemia during chemotherapy. Abstract : Doxorubicin is a first‐line chemotherapy agent on human myelogenous leukemia clinical treatment, but the development of chemoresistance has largely limited curative effect. In this study, we aimed to evaluate the biological function and molecular mechanisms of CrkL to Doxorubicin resistance. We observed that silencing of CrkL could effectively increase apoptosis rate induced by doxorubicin and dramatically reversed doxorubicin resistance in K562/ADR cells. Further studies revealed knockdown CrkL expression suppressed PI3K/Akt/MRP1 signaling, which indicated CrkL siRNA reversed doxorubicin effect through regulating PI3K/Akt/MRP1 signaling. In addition, overexpression of MRP1 could evidently reduce apoptosis rate and reversed the inhibitory effects of doxorubicin resistance caused by CrkL siRNA on K562/ADR cells. In vivo experiments revealed that CrkL silencing suppressed tumor growth of K562/ADR through regulating PI3K/AKT/MRP1 signaling.Together, we indicated that CrkL is up‐regulated in myelogenous leukemia cells and silencing of CrkL could reversed Doxorubicin resistance effectively. These results show a potential novel strategy for intervention chemoresistance in myelogenous leukemia during chemotherapy.